Water's dual nature and its continuously changing hydrogen bonds. (22nd July 2016) - Henchman, Richard H
Abstract: A model is proposed for liquid water that is a continuum between the ordered state with predominantly tetrahedral coordination, linear hydrogen bonds and activated dynamics and a disordered state with a continuous distribution of multiple coordinations, multiple types of hydrogen bond, and diffusive dynamics, similar to that of normal liquids. Central to water's heterogeneous structure is the ability of hydrogen to donate to either one acceptor in a conventional linear hydrogen bond or to multiple acceptors as a furcated hydrogen. Linear hydrogen bonds are marked by slow, activated kinetics for hydrogen-bond switching to more crowded acceptors and sharp first peaks in the hydrogen-oxygen radial distribution function. Furcated hydrogens, equivalent to free, broken, dangling or distorted hydrogens, have barrierless, rapid kinetics and poorly defined first peaks in their hydrogen-oxygen radial distribution function. They involve the weakest donor in a local excess of donors, such that barrierless whole-molecule vibration rapidly swaps them between the linear and furcated forms. Despite the low number of furcated hydrogens and their transient existence, they are readily created in a single hydrogen-bond switch and free up the dynamics of numerous surrounding molecules, bringing about the disordered state. Hydrogens in the ordered state switch with activated dynamics to make the non-tetrahedral coordinations of the disordered state, which can also combine to make the ordered state. Consequently, the ordered and disordered states are both connected by diffusive dynamics and differentiated by activated dynamics, bringing about water's continuous heterogeneity.